Causes of Death and the Mortality Rate of Newborns in NICU in Mashhad for Five Years - Ahmadshah Farhat; Reza Saeidi; Fatemeh soltan Zegheibizadeh; Farideh Golhasani; Ashraf Mohammadzadeh (Mashhad University of Medical Sciences, 2022)
Background: The neonatal period is the riskiest time for child survival. Globally, 2.4 million children died in the first month of life in 2020, and there are approximately 6,700 newborn deaths every day. In this study, the authors have evaluated the causes of death among infants hospitalized in the Neonatal Intensive Care Unit (NICU) of Imam Reza Hospital, Mashhad, Iran, for five years, since 2015. Methods: A cross-sectional study was conducted on all neonates who died in the NICU under study. Data were collected through one of the proposed questionnaires of the Ministry of Health and Medical Education (NOHME), known as the "Green Questionnaire for the Study of the Dead Infant". The data were recorded regarding asphyxia, congenital anomalies, sepsis or infection, respiratory distress syndrome (RDS), disseminated intravascular coagulation, pneumothorax, seizures, and the date of death. The extracted data were categorized and analyzed by the SPSS software (version 16). Babies who died at more than 28 days of age were excluded. Results: Totally, 501 out of 4,348 NICU admissions died (11.52%), 54.5% of whom were male and 45.5% female. The mean birth weight was 1,658±1,018 grams, and the mean gestational age was 32±6 weeks. Most of them were between days one to six. The most common causes of NICU-Mortality Rate (MR) were RDS, congenital heart disease, and congenital anomalies, in descending order. The hospital under study recently expanded to a referral center for congenital heart disease in the east of Iran, which affected the NICU-MR in the ward under study. After the omission of congenital heart disease, the NICU-MR was 10.1%. Conclusion: The NICU-MR was 10.1-11.5% in this study. After RDS, the second cause of death was congenital heart disease. As it is a new division in the hospital under study, it is hoped to get better improvement in congenital heart disease management.